Communication offices in Andalucia: development and strengthening (2003-2022) - Almansa-Martínez, Ana (2024)
The magnitude that communication has acquired today explains, to a large extent, the development experienced by communication offices. Any organization of any kind needs an organizational structure that optimally manages its relations with its relational universe, both externally and internally. This research aims to find out what the current panorama of communication departments is in Andalusia -territorially, one of the largest autonomous communities of Spain- and to discover how it has evolved in the first two decades of the 21st century, taking into account the public, private and social sectors. The results show a generalized growth in the number of communication offices in all provinces and in all sectors, especially those of local administrations, as well as communication companies and social organizations, which have tripled in the last century. In addition to significant changes in the digitalization of communication. Now, Andalusian organizations, in addition to having a website, have profiles on the main social networks.